Self-bonding and the electrochemical properties of silica-coated nanowires composed of cobalt-coordinated peptide bundles. Issue 28 (5th July 2017) - Murai, Kazuki; Yamamoto, Yusuke; Kinoshita, Takatoshi; Nagata, Kenji; Higuchi, Masahiro
Abstract : We propose a method for self-bonding between electrodes by silica-coated peptide nanowire. Abstract : We propose a method for self-bonding between electrodes using the self-organizational processes of a silica-coated peptide hybrid nanowire. We designed and synthesized a 23-mer α-helical peptide having functional sites that serve as catalytic sites for silica mineralization (glutamic acid [Glu] and lysine [Lys]) and binding (serine [Ser]), as well as for the formation of a Co(ii ) ion complex. The peptides formed nanowires composed of α-helical bundles that showed axial connection because of complexation between Co(ii ) and the histidine (His) residues, and macro-dipole interactions of the α-helical peptides. The nanowires self-bonded between the electrodes, and the surface of the nanowires was coated with silica using mineralization. The silica coating of the surface of the Co(ii )-coordinated peptide nanowires induced two kinds of phenomena: (1) structural stabilization of the peptide nanowire component in the composite and (2) an increase in conductivity compared with that of the non-coated peptide nanowires.